Self-Assessment in Writing Competency: Teachers’ Perspectives - Dewi, Ni Luh Putu Meka; Dewi, Ni Luh Putu Eka Sulistia; Nazira, Arni; Wulandari, Ella (Universitas Pendidikan Ganesha, 2024)
Self-assessment is a suitable technique for assessing students’ writing competency. Teachers use self-assessment as the assessment that gives opportunities for the students to assess themselves. It is important because self-assessment allows students to assess themselves. However, in its implementation, the challenges are also faced by the teachers. From that, this study aimed to investigate teachers’ perception of self-assessment in writing competency and the challenges faced by them. This research used a mixed method with an explanatory design that used survey and interview methods to collect the data. Questionnaire data was analyzed using Excel by looking for median values, while interview data was analyzed using thematic analysis. The sample used in 5 English Teachers who had already implemented the self-assessment in writing competency. The findings of this research include, first: teachers have a positive perception on self-assessment that self-assessment, (1) its usefulness for students, (2) it encourages students to write, (3) students are more confident and independent, (4) it helps teachers to monitor the students, and (5) help them to identify the suitable methods in writing. Second, teachers also face some problems in the implementation of self-assessment: (1) students are confused about doing self-assessment, (2) still subjectivity in self-assessment, and (3) teachers still lack technology. It concludes that self-assessment has a positive impact on writing competency, but teachers need to pay attention to the challenges that they face.